HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN KOMITMEN ORGANISASI (Studi pada Karyawan Industri Jasa Konstruksi PT. Multi Structure Duri) - Ronny Fernando Silali; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The problem of this research is declining employee morale PT. Multi Structure Duri. This indicates began to decrease employees' organizational commitment to the company so that employees of PT Multi Structure Duri many who were absent without any reason (alpha).This study aims to determine the application of transformational leadership style, knowing how organizational commitment, and to see the relationship of transformational leadership style and organizational commitment using correlation spreaman. The results showed that there was a very strong relationship between transformational leadership and organizational commitment at PT. Multi Structure Duri, where the results of calculation of correlation coefficient of 0.828.Thus it can be seen that the transformational leadership style has a very strong relationship with the organization's commitment to the employees of PT. Multi Structure Duri.Keywords: transformational leadership, organizational commitment